Compact Heat Integrated Reactor System of Steam Reformer, Shift Reactor and Combustor for Hydrogen Production from Ethanol - Watcharapong Khaodee; Tara Jiwanuruk; Khunnawat Ountaksinkul; Sumittra Charojrochkul; Jarruwat Charoensuk; Suwimol Wongsakulphasatch; Suttichai Assabumrungrat (My University, 2020)
A compact heat integrated reactor system (CHIRS) of a steam reformer, a water gas shift reactor, and a combustor were designed for stationary hydrogen production from ethanol. Different reactor integration concepts were firstly studied using Aspen Plus. The sequential steam reformer and shift reactor (SRSR) was considered as a conventional system. The efficiency of the SRSR could be improved by more than 12% by splitting water addition to the shift reactor (SRSR-WS). Two compact heat integrated reactor systems (CHIRS) were proposed and simulated by using COMSOL Multiphysics software. Although the overall efficiency of the CHIRS was quite a bit lower than the SRSR-WS, the compact systems were properly designed for portable use. CHIRS (I) design, combining the reactors in a radial direction, was large in reactor volume and provided poor temperature control. As a result, the ethanol steam reforming and water gas shift reactions were suppressed, leading to lower hydrogen selectivity. On the other hand, CHIRS (II) design, combining the process in a vertical direction, provided better temperature control. The reactions performed efficiently, resulting in higher hydrogen selectivity. Therefore, the high performance CHIRS (II) design is recommended as a suitable stationary system for hydrogen production from ethanol.
Keywords: Water-gas shift reaction; Multiphysics; Catalysts for Methane Reforming